Hermanson's case ; Olympics ; Hotdog [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Swedisn-German nationals caught by AFP suspected of helping the communist rebels in Quezon Province. A look at the allege anomalies in the Philippine delegation to Seoul Olympics. A look at the originators of the "Manila Sound" the first to bring Pinoy music to rock sound.
Hermanson's case (20 min.) -- Olympics (16 min.) -- Hotdog (11 min.)
VHS.
Keywords: Foreign correspondences -- Philippines; Human rights -- Philippines; Athletes -- Philippines; Bands -- Philippines; Hotdog (Band).